Untold Stories of Future Engineers: Engineering Students’ Reflections in a Fiction-Based Ethics Course. - Andersson, Sara M.; Brodin, Eva M. (Science & Engineering Ethics, 2026)
The integration of micro- and macroethical perspectives remains a challenge in engineering ethics education (EEE). Fiction-based EEE has been advocated as a pedagogical approach that can help students in this regard. However, how students actually use fiction to engage with micro- and macroethics remains underexplored. Therefore, this case study aimed to (1) identify how students’ engagement with fictions connected to micro and macro perspectives on engineering and technology ethics, (2) examine how students realized pedagogical potentials of fiction-based pedagogy in this regard, and (3) explore how the outcomes related to the pedagogical framing and activities of the course. The selected case was an elective, fiction-based EEE course, during which the written course work of students, teacher and student interviews, course materials, and data from workshop observations were collected for qualitative analysis. Findings show that several expected pedagogical potentials of fiction-based pedagogy were realized as students reflected on what guides human behavior and on the societal impact of technology, both within and beyond the fictions. However, students’ reflections rarely connected to their future professional role. These findings could be related to characteristics of the employed pedagogy and fictions, but also to students’ prior knowledge and expectations regarding professional engineering practice. We conclude that students may need targeted support towards connecting fictions with self and profession, and that fiction-based EEE may benefit from recognizing and responding to students’ pre-existing expectations on social responsibility and ethical agency in engineering.